PERFORMAN PERTUMBUHAN DAN KADAR N EKSKRETA DENGAN PENGGUNAAN TEPUNG BAWANG PUTIH DALAM RANSUM AYAM PEDAGING - Marfuah, Nuun; Hafsah, Hafsah (FAPETKAN UNTAD, 2011)
This experiment was designed to study effects of including garlic powder in a diet on the growth and nitrogen contents of excreta in broiler chicken. A total of 100 day old chicks was used and confined in 20 cages during the experiment during which they were fed on a diet consisting of mixture of ground corn, rice bran, ground soybean, fish meal, copra meal, topmix and garlic powder.The animals were arranged in a completely randomized design with five dietary treatments each of which was repeated four times. The dietary treatments tested were the inclusion leves of garlic powder in diets: 0% (R0), 1.5% (R1), 3% (R2), 4.5% (R3) and 6% (R4). The chickens were allowed to gow for 42 d during which fresh drinking water was also always available. Data on growth performance and nitrogen contents of excreta were analyzed with an analysis of variance. Results indicated that the dietary treatment affected (P<0.01) broiler’s body weight gain, feed conversion and nitrogen content of the excreta, but it did not affect (P>0.05) feed intake. The best results on growth rate (2,348.70g) and feed conversion (1.59) were found for R3. Nitrogen content of excreta was lower by 61.71% for treatment R4 in comparison to control treatment. Key words: Broiler, diet, excreta, garlic, growth.